Development of children of 2 – 3 years old from pre-prosperous family and prosperous family stage II - Haris Marta Saputra; Sulaiman Yusuf; Noval Azis; Amir Syarifuddin; Bistok Saing (Paediatrica Indonesiana, 2001)
In this study we assess the condition of children development of 2-3 years of age in prosperous family, preprosperousfamily and prosperous family stage II, and find the related factors. This was a cross sectional study on 94children of pre-prosperous family and 94 children of prosperous family stage II at Medan Tuntungan district from December1998 up to March 1999. Data is obtained by questionnaires and examination of the developmental bases by Denver II Method.Statistical analysis of relationship between 2 qualitative variables is tested by chi-square. In the pre-prosperous family wefound 67 children with (35.6%) normal development and 27 (14.4%) children with abnormal development, on the prosperousfamily stage II there were 81 (43.1%) children with normal development and 13 (6.9%) children with abnormal development.We found significant difference between the children development of pre-prosperous and prosperous stage II (p<0.05),significant relationship between children development within 2-3 years of age and the parents’ education level of the Preprosperousfamily (p<0.05), and no significant relationship of the following factors: mothers employment status, mother’sage, number of family and the child’s order in the family.